2017
DOI: 10.4155/fsoa-2017-0077
|View full text |Cite|
|
Sign up to set email alerts
|

Recent progress in the research of cold-inducible RNA-binding protein

Abstract: Cold-inducible RNA-binding protein (CIRP) is a cold-shock protein which can be induced after exposure to a moderate cold-shock in different species ranging from amphibians to humans. Expression of CIRP can also be regulated by hypoxia, UV radiation, glucose deprivation, heat stress and H2O2, suggesting that CIRP is a general stress-response protein. In response to stress, CIRP can migrate from the nucleus to the cytoplasm and regulate mRNA stability through its binding site on the 3′-UTR of its targeted mRNAs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
121
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(124 citation statements)
references
References 98 publications
2
121
0
Order By: Relevance
“…Cold‐inducible RNA‐binding protein (CIRP) was first described in the late 1990s as an RNA chaperone controlling the expression of cell‐cycle proteins in hibernating animals . Since then, intense research on intracellular CIRP (iCIRP) has revealed its role in the regulation of a variety of cellular stress responses, including mRNA stability, cell proliferation, cell survival, circadian clock gene modulation, telomerase maintenance, stress adaptation, and tumor formation and progression . These iCIRP activities, which allow cells to cope with various cellular stress conditions, have been reviewed in detail .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cold‐inducible RNA‐binding protein (CIRP) was first described in the late 1990s as an RNA chaperone controlling the expression of cell‐cycle proteins in hibernating animals . Since then, intense research on intracellular CIRP (iCIRP) has revealed its role in the regulation of a variety of cellular stress responses, including mRNA stability, cell proliferation, cell survival, circadian clock gene modulation, telomerase maintenance, stress adaptation, and tumor formation and progression . These iCIRP activities, which allow cells to cope with various cellular stress conditions, have been reviewed in detail .…”
Section: Introductionmentioning
confidence: 99%
“…Since then, intense research on intracellular CIRP (iCIRP) has revealed its role in the regulation of a variety of cellular stress responses, including mRNA stability, cell proliferation, cell survival, circadian clock gene modulation, telomerase maintenance, stress adaptation, and tumor formation and progression . These iCIRP activities, which allow cells to cope with various cellular stress conditions, have been reviewed in detail . In contrast to iCIRP, extracellular CIRP (eCIRP) was recently discovered to act as a damage‐associated molecular pattern (DAMP) promoting inflammation and injury .…”
Section: Introductionmentioning
confidence: 99%
“…CIRBP is an 18-kDa protein that consists of an N-terminal RNA recognition motif (RRM) domain and a C-terminal arginine-glycine rich motif. CIRBP upregulation is observed in various tissues upon mild hypothermia, cold stress, UV radiation, mild hypoxia, and glucose deprivation (13). CIRBP serves its function by binding specific 51 nucleotides-long U-rich motifs in the 3'-untranslated region (3'-UTR) of mRNA transcripts (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…The exposure to mild hypothermic temperatures induces the expression of cold‐shock proteins (Liao, Tong, Tang, & Wu, ). CIRBP, also called CIRP and A18 hnRNP, is a constitutively expressed cold‐shock protein highly conserved among different species whose expression is present in a large variety of tissues and cells, including the ovaries among others (Zhong & Huang, ). CIRBP is involved in several cellular processes such as cellular proliferation and cell survival, and it is involved in anti‐apoptotic and anti‐senescence pathways (Liao et al., ; Zhong & Huang, ).…”
Section: Introductionmentioning
confidence: 99%
“…CIRBP, also called CIRP and A18 hnRNP, is a constitutively expressed cold‐shock protein highly conserved among different species whose expression is present in a large variety of tissues and cells, including the ovaries among others (Zhong & Huang, ). CIRBP is involved in several cellular processes such as cellular proliferation and cell survival, and it is involved in anti‐apoptotic and anti‐senescence pathways (Liao et al., ; Zhong & Huang, ). These findings suggest that the induction of CIRBP during in vitro maturation (IVM) of oocytes could improve cryotolerance to vitrification procedures.…”
Section: Introductionmentioning
confidence: 99%